2015
DOI: 10.1002/erv.2354
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Oxytocin Receptor Gene Polymorphism (rs53576) and Bulimia Nervosa

Abstract: These findings suggest the involvement of the oxytocinergic system in the mechanism that underlies BN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…Rs237897(A) is part of a haplotype related to ASD 27 , altruism in males 30 , lower self-reported betrayal levels 71 , continuous social connectedness 72 , and Theory of Mind 18 . Alleles of rs53576 have been reported in several studies: the G allele has been reported to be implicated in Bullimia Nerviosa 73 , but also in diminished stress after social support 74 , adult separation anxiety 75 , oxytocin sensitivity in social cooperation settings (increased in males, decreased in females) 76 , overall weak social cognition skills in ADHD patients 25 and facial recognition deficits 53 . MHS rs53576(A) might be involved in AS 27, 45 , higher empathic performanc 77, 78 and social connectedness in women 31 , but also lower psychological resources such as self-esteem, optimism and emotional mastery 79 .…”
Section: Resultsmentioning
confidence: 99%
“…Rs237897(A) is part of a haplotype related to ASD 27 , altruism in males 30 , lower self-reported betrayal levels 71 , continuous social connectedness 72 , and Theory of Mind 18 . Alleles of rs53576 have been reported in several studies: the G allele has been reported to be implicated in Bullimia Nerviosa 73 , but also in diminished stress after social support 74 , adult separation anxiety 75 , oxytocin sensitivity in social cooperation settings (increased in males, decreased in females) 76 , overall weak social cognition skills in ADHD patients 25 and facial recognition deficits 53 . MHS rs53576(A) might be involved in AS 27, 45 , higher empathic performanc 77, 78 and social connectedness in women 31 , but also lower psychological resources such as self-esteem, optimism and emotional mastery 79 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, no differences were found in basal or stimulated peripheral levels of oxytocin in women with bulimia nervosa compared with controls 65,68 . In the past 5 years, studies in women have identified associations between genetic variation in the oxytocin receptor and eating disorder diagnosis (bulimia nervosa) 70 , eating disorder thoughts and behaviours (in those with anorexia nervosa as well as a community sample of women) 71-73 , food preoccupation (in anorexia nervosa) 71 and reported nutrient intake (in a community sample of women) 72 .…”
Section: Eating Behaviourmentioning
confidence: 99%
“…Two recent studies have investigated associations between OXT‐R genetic variants and ED. In particular, a Korean study showed a positive association between the G allele of rs53576 and bulimia nervosa (BN) in a clinical sample of 90 women with BN compared to controls ( n = 103) (Kim, Kim, Kim, Shin, & Treasure, 2015). Amongst patients with AN, AN (weight‐recovered), BN and controls (overall n = 124), subjects with rs53576 and rs2254298 GG/GG haplotype had lower scores on overall ED psychopathology measures, less body shape and food preoccupation, fewer obsessive compulsive behaviours, and lower anxiety (Acevedo, Valencia, Lutter, & McAdams, ).…”
Section: Introductionmentioning
confidence: 99%